ANALISIS PENGARUH FINANCIAL PERFORMANCE, PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), INSIDER OWNERSHIP, FIRM SIZE, DIVIDEND POLICY DAN PROPORSI KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Periode 2010-2015) - Panggabean, Deo; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2017)
This research purposes to indentify the main factors influencing firm value that proxied by Price Book Value (PBV) especially in manufacturing companies sector listed on the Indonesian Stock Exchange (IDX) during period 2010-2015.The population of this research consists of manufacturing companies listed on the IDX period 2010-2015. This research used secondary data anda used purposive sampling method in determining the sample. The total of sample in this case are 50 companies. Multiple regression is used as the analysis technique in this research.The study documents the positive significant of financial performance, firm size, dividend policy and proportion of independent commissioner on firm value. While the disclosure of corporate social responsibility and insider ownership found influental positive but insignificant to firm value.